Occurrence of inflammatory bowel disease in patients with chronic inflammatory skin diseases: a cohort study. (3rd August 2022) - Schneeweiss, Maria C.; Kirchgesner, Julien; Wyss, Richard; Jin, Yinzhu; York, Cassandra; Merola, Joseph F.; Mostaghimi, Arash; Silverberg, Jonathan I.; Schneeweiss, Sebastian; Glynn, Robert J.
Abstract: Background: Several studies have linked various chronic inflammatory skin diseases (CISDs) with inflammatory bowel disease (IBD) in a range of data sources with mixed conclusions. Objectives: We compared the incidence of IBD – ulcerative colitis (UC) and Crohn disease (CD) – in patients with a CISD vs. similar persons without a CISD. Methods: In this cohort study using nationwide, longitudinal, commercial insurance claims data from the USA, we identified adults and children who were seen by a dermatologist between 2004 and 2020, and diagnosed with either psoriasis, atopic dermatitis, alopecia areata, vitiligo or hidradenitis suppurativa. Comparator patients were identified through risk‐set sampling; they were eligible if they were seen by a dermatologist at least twice and not diagnosed with a CISD. Patient follow‐up lasted until either IBD diagnosis, death, disenrolment or end of data stream, whichever came first. IBD events, UC or CD, were identified via validated algorithms: hospitalization or diagnosis with endoscopic confirmation. Incidence rates were computed before and after adjustment via propensity‐score decile stratification to account for IBD risk factors. Hazard ratios (HR) and 95% confidence intervals (CIs) were estimated to compare the incidence of IBD in CISD vs. non‐CISD. Results: We identified patients with atopic dermatitis ( n  = 123 614), psoriasis ( n  = 83 049), alopecia areata ( n  = 18 135), vitiligo ( n  = 9003) or hidradenitis suppurativa ( n  = 6806), and comparator patients without a CISD ( n  = 2 376 120). During a median follow‐up time of 718 days, and after applying propensity‐score adjustment for IBD risk factors, we observed increased risk of both UC (HRUC 2·30, 95% CI 1·61–3·28) and CD (HRCD 2·70, 1·69–4·32) in patients with hidradenitis suppurativa, an increased risk of CD (HRCD 1·23, 1·03–1·46) but not UC (HRUC 1·01, 0·89–1·14) in psoriasis, and no increased risk of IBD in atopic dermatitis (HRUC 1·02, 0·92–1·12; HRCD 1·08, 0·94–1·23), alopecia areata (HRUC 1·18, 0·89–1·56; HRCD 1·26, 0·86–1·86) or vitiligo (HRUC 1·14, 0·77–1·68; HRCD 1·45, 0·87–2·41). Conclusions: IBD was increased in patients with hidradenitis suppurativa. CD alone was increased in patients with psoriasis. Neither UC nor CD was increased in patients with atopic dermatitis, alopecia areata or vitiligo. What is already known about this topic? Several studies have linked various chronic inflammatory skin diseases (CISDs) with inflammatory bowel disease (IBD) utilizing a range of data sources, with mixed conclusions. What does this study add? This large‐scale, claims‐based cohort study expands current knowledge by providing background rates for IBD across multiple CISDs using consistent methods and within a single, nationally representative patient population. We observed a relative increased risk of IBD in patients with hidradenitis suppurativa, but the overall incidence rate difference of IBD was generally low. Crohn disease alone was significantly increased in patients with psoriasis, and neither ulcerative colitis nor Crohn disease was increased in patients with atopic dermatitis, vitiligo or alopecia areata. Abstract : This is a large‐scale analysis of claims data from a representative dermatology patient population. We observed that IBD was increased in patients with hidradenitis suppurativa; Crohn's disease alone was significantly increased in patients with psoriasis; neither ulcerative colitis nor Crohn's disease was increased in patients with atopic dermatitis, vitiligo or alopecia areata. Linked Comment: N.A. Levin and M. Rashighi. Br J Dermatol 2022; 187:631–632 . Plain language summary available online